Dissent : The Issue of Modern Art in Boston. - Buchloh, Benjamin H.D.; Guilbaut, Serge; Heller, Reinhold; Joselit, David; Ross, David A.; Sussman, Elisabeth; The Institute of Contemporary Art Boston (Boston : Institute of Contemporary Art Boston, 1985)
Scharl, Josef ; Dix, Otto ; Kirchner, Ernst Ludwig ; Nolde, Emil ; Heckel, Erich ; Kolbe, Georg ; Marc, Franz ; Beckmann, Max ; Kokoschka, Oskar ; Munch, Edvard ; Ensor, James ; Gropper, William ; Hartley, Marsden ; Morris, George L.K. ; Pollock, Jackson ; Kuhn, Walt ; Avery, Milton ; Hirschfield, Morris ; Davis, Stuart ; Baziotes, William ; Burtin, Paul ; Marin, John ; Sloan, John ; Stuempfig, Walter ; McIver, Loren ; Knaths, Karl ; Tobey, Mark ; Benton, Thomas ; Gorky, Arshile ; Watts, Robert ; Duchamp, Marcel ; Oldenburg, Claes ; Levine, Sherrie ; Lawler, Louise ; Nagy, Peter ; McCollum, Allan ; Holzer, Jenny
Dissent: The Issue of Modern Art in Boston : A series of three exhibitions : The Expressionist Challenge, December 5, 1985 - February 9, 1986 / Revolt in Boston: Fear vs. Freedom, February 18 - April 20, 1986 / As Found, April 29 - June 22, 1986 in The Institute of Contemporary Art, Boston
Engels
boek
Keywords: Boston